Rancangan Aplikasi Bidang Keilmuan Desain Komunikasi Visual pada Kegiatan Community Outreach Program - Natadjaja, Listia (Nirmana, 2012)
Petra Christian University has conducted Community Outreach Program (COP) to improve the welfare of society especially in Kediri district. The activities in COP are not only focused on the physical but also non physical program. Unfortunately, design field doesn’t seem to attract much attention in practice, but if we analyze and observe there are many designers’ roles that can refine this COP program. This paper is made because of my concerns about the lack of the application in scientific field of Visual Communication Design. I try to explore many things that can be done by Visual Communication Design students and how they can play an important role in COP program. In the future, the Visual Communication Design students are expected to be more active in COP program and their designs’ works can give more impact to the society.